Firms' Exports, Volatility and Skills: Evidence from France - Maria Bas; Pamela Bombarda; Sébastien Jean; Gianluca Orefice (Center for Economic Studies and ifo Institute (CESifo), 2019)
Inequalities between workers of different skills have been growing in the era of globalization. Firms' internationalization mode has an impact on job stability. Exporting firms are not only exposed to different foreign shocks, they also pay skill-intensive fixed costs to serve foreign markets. This implies that, for larger exporters, the labor demand for skilled workers is expected to be less volatile than for unskilled workers. In this paper we study the relationship between firms' export activity and job stability across employment skills. Relying on detailed firm-level data from France for the period 1996-2007, we show that firms with higher export intensity exhibit a lower volatility of skilled labor demand relative to the volatility of unskilled labor demand. Our identification strategy is based on an instrumental variable approach to provide evidence on the causal effect of the export performance of the firm on the volatility of employment of different skills. Our findings suggest that exporting increases the stability of skilled jobs, but feeds the precariousness of unskilled ones.
Keywords: F10; F16; L25; L60; 330; exports; employment volatility; skilled labor; firm-level data